2015
DOI: 10.1016/j.ultsonch.2014.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic transformation of micelle structures: Effect of frequency and power

Abstract: A comprehensive investigation on the effect of ultrasonic frequency and power on the structural transformation of CTABr/NaSal micelles has been carried out. Sonication of this micelle system at various ultrasonic frequencies and power resulted in the formation and separation of two types of micelles. High viscoelastic threadlike micelles of ∼ 2 nm in diameter and several μm in length and tubular micelles possessing a viscosity slightly above that of water with ∼ 30-50 nm diameter and few hundred nm length. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…The use of high energy systems, like sonication, for the formation of micelles and nanoemulsions is a well explored methodology (Kumar and Kumar, 2018;Loureiro et al, 2016;Noro et al, 2017;Yusof and Ashokkumar, 2015), although no reports have been found describing the use of this method for the formation of PTS micelles. We investigated the application of sonication, mainly aiming to avoid the use of an organic solvent in the system.…”
Section: Micelles Productionmentioning
confidence: 99%
“…The use of high energy systems, like sonication, for the formation of micelles and nanoemulsions is a well explored methodology (Kumar and Kumar, 2018;Loureiro et al, 2016;Noro et al, 2017;Yusof and Ashokkumar, 2015), although no reports have been found describing the use of this method for the formation of PTS micelles. We investigated the application of sonication, mainly aiming to avoid the use of an organic solvent in the system.…”
Section: Micelles Productionmentioning
confidence: 99%
“…It is reported that the rate of radical production is the lowest at 20 kHz and follows the order 20 kHz < 1062 kHz < 647 kHz < 358 kHz < 213 kHz [24]. The images of gold nanoparticles shown on the right show that the particle shape could be controlled, when HIFU is used under different experimental conditions [25].…”
Section: Nanomaterials Including Polymersmentioning
confidence: 95%
“…Using a similar strategy, a variety of metal nanoparticles that include Ag, Cu, Pt, Rh, etc. have been sonochemically synthesised [19][20][21][22][23][24][25]. The choice of experimental conditions seem to affect the shape and size of nanoparticles generated.…”
Section: Nanomaterials Including Polymersmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there have not yet been any direct measurements of high-χ N chain exchange from CIE to evaluate the expected rate dependencies. We note that sonication has been used to induce micelle structure changes, to break extended polymer assemblies , and micellar aggregates, and to disperse additives into micelles. Lastly, we note that ultrasonic absorption spectroscopy was used to study SCE rates for dynamic small-molecule surfactants. To the best of our knowledge, polymer exchange has not yet been directly measured as a result of ultrasonic cavitation under kinetically controlled, high-χ N conditions.…”
Section: Introductionmentioning
confidence: 99%